1963
DOI: 10.1144/gsjgs.119.1.0243
|View full text |Cite
|
Sign up to set email alerts
|

The Lewisian complex of South Harris With some observations on the metamorphosed basic intrusions of the Outer Hebrides, Scotland

Abstract: The metamorphic petrology and history of the Lewisian rocks of South Harris are described. The paragneisses in each of the two main belts are divided into three lithological and possibly stratigraphical units, the disposition of which indicates folding in tight plunging isoclines along Nw–Se (Early Laxfordian) axes. Relic textures indicating an early (pre-Lax-fordian) metamorphism and folding are recognizable in the paragneisses and also in the pyroxene-granulites… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

1966
1966
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(18 citation statements)
references
References 35 publications
0
18
0
Order By: Relevance
“…The grain size of the HGB pegmatites is highly variable, but locally can be extremely coarse, with feldspar crystals up to 1 m in length. The HGB pegmatites commonly have very sharp, planar contacts with the host rock and are highly discordant to the country-rock foliation, which broadly trends NW-SE (Jehu and Craig, 1927;Dearnley, 1963;Mason, 2015) (Fig. 3c).…”
Section: Harris Granulite Belt (Hgb)mentioning
confidence: 99%
See 2 more Smart Citations
“…The grain size of the HGB pegmatites is highly variable, but locally can be extremely coarse, with feldspar crystals up to 1 m in length. The HGB pegmatites commonly have very sharp, planar contacts with the host rock and are highly discordant to the country-rock foliation, which broadly trends NW-SE (Jehu and Craig, 1927;Dearnley, 1963;Mason, 2015) (Fig. 3c).…”
Section: Harris Granulite Belt (Hgb)mentioning
confidence: 99%
“…2) comprises the Leverburgh Belt and the South Harris Igneous Complex (SHIC) (Fettes et al, 1992). The Leverburgh Belt is made up of strongly foliated, NW-SE trending metasedimentary rocks dominated by garnet-bearing, quartzrich gneisses with subordinate pelitic, semi-pelitic and quartzitic lithologies, and lenses of marble, graphitic schist and mafic material (Dearnley, 1963;Dickinson, 1974;Fettes et al, 1992;Baba, 1998). The SHIC is a zone of coarse-grained meta-igneous rocks (meta-anorthosite, metadiorite, metagabbro and metanorite) (Dearnley, 1963;Witty, 1975;Cliff et al, 1983;Fettes et al, 1992).…”
Section: Harris Granulite Belt (Hgb)mentioning
confidence: 99%
See 1 more Smart Citation
“…The reason for the presence of various types of high Mg rocks in such a narrow area is probably due to variety of precursory rocks in South Harris. On the basis of lithological assemblage and geochemical characteristics of mafic gneiss having basic composition, the Leverburgh belt in the South Harris complex can be divided into three lithological series, namely, Benn Obbe Series (A and B), Rodel Series, and Chaipaval Pelitic Series (Dearnley, 1963;Baba, 1997). Their precursory rocks and tectonic setting were interpreted to be as trench type sediments with arc type volcanics (Benn Obbe Series A and B), mélange with oceanic type volcanics (Rodel Series), and trench hemipelagic sediments with ocean type volcanics (Chaipaval Pelitic Series) (Baba, 1997;2002).…”
Section: Uht Metamorphism In the South Harris Complexmentioning
confidence: 99%
“…Dearnley (1963) showed that in a traverse northwards from the southern coast, five main lithological units are present. These are pyroxenegranulites, paragneisses (the Leverburgh Belt), an intermediate-basic-ultrabasic igneous suite, a second belt of paragneisses (the Langavat Belt) and an acidic injection complex.…”
Section: Introductionmentioning
confidence: 99%